Effect of rainfall infiltration on the hydraulic response and failure mechanisms of sandy slope models - Montoya-Domínguez, Juan David; García-Aristizábal, Edwin Fabián; Vega-Posada, Carlos Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper presents experimental results obtained from silty sand slope models subjected to an artificial rainfall. Four models were constructed to evaluate the effect of initial water content and rainfall intensity on the hydraulic behavior and failure mechanisms of the slopes. The models were instrumented with volumetric water content sensors to monitor the advance of the water front, and inclinometers to measure lateral movements of the slope. The models were subjected to rainfall intensities ranging from 25 to 50 mm/h, and durations from 19 to 152 minutes. The influence of low intensity rainfall events before a high intensity rainfall is discussed herein. The results showed that the time the slope models required to reach failure was influenced by the soil initial water content, being shorter at high initial water contents. These results are useful to understand the behavior of unsaturated natural slopes and embankments exposed to rainfall infiltration, and to complement the existing laboratory database existing in this subject.